PERAN REMAJA MASJID TERHADAP INKLINASI MORAL REMAJA DI LINGKUNGAN MASJID DARUSSALAM BANTUR - Muhammad Arif Nasruddin, Arfan Ramadhani, Sunarto (PRODI PAI FIK UNIRA MALANG, 2023)
There are many incidents or cases of moral decline in our surroundings, of course here youth in the mosque is an organization that has enormous potential to influence young people in their surroundings, because it has support with many youth members, it is hoped that it can influence and change moral values. youth in their environment with various efforts. In this study, the authors used a qualitative research method with a type of case study on mosque youth who had various attempts to overcome this problem.This study shows the forms of moral decline that occur in adolescents at the Darussalam Bantur Mosque, such as sexual violations, acts of bullying, consuming alcohol, theft, and speeding or illegal racing. Then there was an increase in morale with many teenagers who began to feel ashamed when they did wrong actions, many of them began to participate with youth members of the mosque, to actively participate in various youth activities in the mosque. The initial action taken by the youth of the mosque was by inviting local youths to join the youth members of the mosque, then carrying out various routine activities. When trying to improve morale, mosque youth also have supporters from various parties, namely the trust of the mosque takmir, the enthusiasm of the surrounding community, the leadership factor that motivates the youth members of the mosque. The obstacles are from the lack of attention from the parents of the teenagers, the social environment factors of the teenagers, then from the sophistication of technology that affects teenagers, and the internal factors of the members who sometimes differ from one another.